Analysis of Factors Affecting Employee Performance at the Regional Planning, Research, and Development Agency (BAPPEDA) of Wakatobi Regency, Southeast Sulawesi Province - Osiani Osiani; Muh. Nur; Sri Wahyuni (Pustaka Digital Indonesia, 2026)
Employee performance is a critical factor in ensuring the effectiveness of public sector organizations, particularly government agencies responsible for regional development planning. Preliminary observations at the Regional Planning, Research, and Development Agency (BAPPEDA) of Wakatobi Regency indicated several performance-related issues, including inadequate work motivation, limited job satisfaction, inconsistent work discipline, and suboptimal working conditions. Although previous studies have examined employee performance in various organizational settings, limited research has simultaneously analyzed work motivation, job satisfaction, work discipline, and work environment within regional government planning institutions. This study addresses this gap by examining the influence of these four factors on employee performance at BAPPEDA Wakatobi Regency. This study employed a quantitative approach with a saturated sampling technique involving all 43 employees as respondents. Data were collected through structured questionnaires, observation, and documentation, and were analyzed using multiple linear regression. The results showed that work motivation, job satisfaction, work discipline, and work environment each had a positive and significant effect on employee performance. Work motivation provided the strongest contribution, followed by work discipline, job satisfaction, and work environment. The coefficient of determination indicated that these four variables explained 57.5% of the variation in employee performance, while the remaining 42.5% was influenced by other factors outside the model. These findings highlight that improving employee performance in regional government institutions requires an integrated human resource management strategy. Strengthening motivation, enhancing job satisfaction, enforcing work discipline, and improving workplace conditions are essential to support more effective, accountable, and responsive public service performance at BAPPEDA Wakatobi Regency.